EDUCATION AND ECONOMIC GROWTH OF THE WESTERN BALKANS COUNTRIES - Erić, Ognjen (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2018)
Numerous theoretical and empiric studies investigate the correlation between education and human capital and economic development. Full affirmation of knowledge and the role of education in stimulating economic growth were provided by endogenous theory. The subject of this paper is to analyse the correlation between education and educational system and the economic growth of the Western Balkans countries (WB). The hypothesis of this work says that: education and educational system in the WB aﬀect the growth of GDP per capita. A better education system stimulates and accelerates the economic growth and development. The aim of this research is to prove that an optimal education system stimulates the growth and development in each observed national economy. In this paper, the results of the correlation analysis indicate high compliance of higher education with GDP per capita i.e. higher education population is particularly important for the level of development whereas there is a highly compliant but inverse relation of the population with informal level of education and economic development in the WB countries.